3D Hierarchical Nanorod@Nanobowl Array Photoanode with a Tunable Light‐Trapping Cutoff and Bottom‐Selective Field Enhancement for Efficient Solar Water Splitting. Issue 14 (28th February 2019) - Tang, Songtao; Li, Mingyang; Huang, Duan; Qiu, Weitao; Xiao, Shuang; Tong, Yexiang; Yang, Shihe
Abstract: Constructing 3D nanophotonic structures is regarded as an effective means to realize both efficient light absorption and efficient charge separation. However, most of the 3D structures reported so far enhance light trapping beyond the absorption onset wavelength, and thus greatly attentuate or even completely block the long‐wavelength light, which could otherwise be efficiently absorbed by narrow‐bandgap materials in a Z‐scheme or tandem device. In addition, constructing a 3D conductive substrate often involves complex processes causing increased cost and upscaling problems. To overcome these shortcomings, a novel 3D hematite nanorod@nanobowl array nanophotonic structure is designed and fabricated by a low‐cost method. This unique structure can enhance light absorption with tunable cutoffs and rationally concentrate photons right above the bowl bottom, enabling efficient charge separation. By loading NiFeOx as a cocatalyst, a high photocurrent density of 3.41 ± 0.2 mA cm −2 at 1.23 V versus reversible hydrogen electrode (RHE) can be obtained, which is 2.35 times that with a planar structure in otherwise the same system. Abstract : A 3D hierarchical nanorod@nanobowl array shows greatly enhanced light absorption and a tunable absorption edge. A cut‐off enhanced absorption can be achieved through reasonable regulation of the nanobowl size. More importantly, uniform light distribution is transformed into in‐bowl light concentration after the plane is shaped into a 3D NR@NB nanostructure.